Managing athletes with palpitations of unknown origin with an external loop recorder: a cohort study - Sciarra, L.; Cavarretta, E.; Siciliani, S.; Sette, A.; Scarà, A.; Grieco, D.; De Ruvo, E.; Palamà, Z.; Nesti, M.; Romano, S.; Penco, M.; Pelliccia, A.; et al. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Palpitations in athletes are usually benign, but the presence of major cardiac arrhythmias should be ruled out despite the infrequent appraisal of symptoms. External loop recorders (ELR) are promising to identify arrhythmias in these circumstances, but experiences in athletes are lacking. We aimed to investigate the feasibility and diagnostic yield of an ELR in athletes with unexplained palpitations in a cohort study. METHODS: One hundred twenty-two consecutive subjects (61 athletes and 61 sedentary controls) with sporadic palpitations and inconclusive diagnosis were enrolled and equipped with an ELR. Findings were categorized as major and minor arrhythmic findings, non-arrhythmic findings or negative monitoring. RESULTS: Long-term ELR monitoring was feasible in all subjects, with median duration of 12 (11; 15) days. Major arrhythmic events during palpitations were found in 9 (14.8%) athletes: 7 experienced sustained paroxysmal supraventricular tachycardia, and 2 had non sustained ventricular tachycardia. Minor arrhythmic events (premature supraventricular or ventricular beats) were observed in 13 athletes (21.3%). Non-arrhythmic findings (i.e., sinus rhythm or sinus tachycardia) were recorded in 28 athletes (45.9%), whereas 11 (18%) had negative monitoring. In the sedentary group, arrhythmic events were similar for types and frequency to athletes. The diagnostic yield of loop monitoring was 82.8% in the overall population and 82.0% in the athlete`s group. CONCLUSIONS: In the management of an athlete symptomatic with unexplained palpitations after 24-hour ECG monitoring and stress test, ELR is an efficient tool to identify major arrhythmic events, which can be present in up to 10% of symptomatic athletes during practice and competition.